Identification of Erwinia species isolated from apples and pears by differential PCR - Gehring, Isabel; Geider, Klaus (Journal of microbiological methods, 2012)
Many pathogenic and epiphytic bacteria isolated from apples and pears belong to the genus Erwinia; these include the species E. amylovora, E. pyrifoliae, E. billingiae, E. persicina, E. rhapontici and E. tasmaniensis. Identification and classification of freshly isolated bacterial species often requires tedious taxonomic procedures. To facilitate routine identification of Erwinia species, we have developed a PCR method based on species-specific oligonucleotides (SSOs) from the sequences of the housekeeping genes recA and gpd. Using species-specific primers that we report here, differentiation was done with conventional PCR (cPCR) and quantitative PCR (qPCR) applying two consecutive primer annealing temperatures. The specificity of the primers depends on terminal Single Nucleotide Polymorphisms (SNPs) that are characteristic for the target species. These PCR assays enabled us to distinguish eight Erwinia species, as well as to identify new Erwinia isolates from plant surfaces. When performed with mixed bacterial cultures, they only detected a single target species. This method is a novel approach to classify strains within the genus Erwinia by PCR and it can be used to confirm other diagnostic data, especially when specific PCR detection methods are not already available. The method may be applied to classify species within other bacterial genera.
Gesehen am 26.04.2018